Dynamic capabilities and marketing capabilities in Portugal - Dias, Á. (2020)
Purpose – The purpose of this paper is to offer an operationalization of an aggregate construct and a decisive contribution to building a dynamic capabilities theory with marketing implications. The authors investigate the influence of dynamic capabilities, specifically routine creation through embedding learning and knowledge, on marketing capabilities and performance in Portugal. The authors examine the direct relationship between dynamic capabilities and marketing capabilities, which is indirectly linked to performance depending on the effectiveness of the resulting new resource configuration. Design/methodology/approach – The authors used four construct dimensions: knowledge creation routines, knowledge transfer processes, marketing capabilities, and firm performance. The study was based on an inter-industry random sample of firms selected from a commercial list. During a nine-month period the authors gathered data from a questionnaire delivered in hand to participating firms and collected through in-depth personal interviews. It was filled out by directors of Portuguese firms who agreed to participate in this study. Findings – First, dynamic capabilities play an important role in the evolution of marketing capabilities and the maintenance of competitive advantage. Specifically, the authors identified a link between knowledge creation routines and knowledge transfer processes with marketing capabilities. Second, the effect of dynamic capabilities on performance can be considered to be substantially indirect. However, the results also show a direct link between knowledge transfer and performance. Originality/value – First, the development of a model establishing the contribution to the evolution of marketing capabilities in order to compete in a changing environment, considering the critical effect of knowledge creation and transfer in a non-static market configuration. Second, the analysis of marketing capabilities from different layers, from strategic to more operational aspects.